2015
DOI: 10.1002/eco.1602
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of hydrologic models for ecological flows and water availability

Abstract: Robust hydrologic models are needed to help manage water resources for healthy aquatic ecosystems and reliable water supplies for people, but there is a lack of comprehensive model comparison studies that quantify differences in streamflow predictions among model applications developed to answer management questions. We assessed differences in daily streamflow predictions by four fine‐scale models and two regional‐scale monthly time step models by comparing model fit statistics and bias in ecologically relevan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 56 publications
2
65
0
Order By: Relevance
“…This finding confirms the findings of previous studies (e.g., Hingray et al, 2010;Westerberg et al, 2011;Murphy et al, 2013;Olsen et al, 2013;Pfannerstill et al, 2014;Shrestha et al, 2014;Caldwell et al, 2015;Vis et al, 2015) and points out the importance of making a careful choice of the objective function for model calibration. I Multi showed little change compared to calibrations with R eff brings into question the benefit of including SFCs in model calibration instead of applying a traditional calibration approach when aiming at estimating a suite of SFCs.…”
Section: On the Importance Of The Choice Of The Objective Functionsupporting
confidence: 91%
See 4 more Smart Citations
“…This finding confirms the findings of previous studies (e.g., Hingray et al, 2010;Westerberg et al, 2011;Murphy et al, 2013;Olsen et al, 2013;Pfannerstill et al, 2014;Shrestha et al, 2014;Caldwell et al, 2015;Vis et al, 2015) and points out the importance of making a careful choice of the objective function for model calibration. I Multi showed little change compared to calibrations with R eff brings into question the benefit of including SFCs in model calibration instead of applying a traditional calibration approach when aiming at estimating a suite of SFCs.…”
Section: On the Importance Of The Choice Of The Objective Functionsupporting
confidence: 91%
“…These results are consistent with those of Olsen et al (2013), Caldwell et al (2015), Vis et al (2015), and Kiesel et al (2017) and can partly be explained by the model behavior characterized by a less pronounced runoff response to precipitation events but increased groundwater discharge to the stream during drier periods compared to the observed data (Vis et al, 2015). The observations that average flow conditions are better simulated than extremes (Caldwell et al, 2015;Vis et al, 2015) or that high-flow-related SFCs are more accurately estimated than those related to low flow (Shrestha et al, 2014;Ryo et al, 2015) cannot be confirmed with our results. None of these earlier studies explicitly included SFCs in model calibration and the deviating results could be attributed to the differing approaches to defining the objective function(s).…”
Section: Model Performance Regarding Sfcssupporting
confidence: 82%
See 3 more Smart Citations